Intragastric bacterial activity and nitrosation before, during, and after treatment with omeprazole. Issue 6447 (22nd September 1984) - Sharma, B K; Santana, I A; Wood, E C; Walt, R P; Pereira, M; Noone, P; Smith, P L; Walters, C L; Pounder, R E
Abstract : Ten healthy volunteers were studied before, during, and after treatment with omeprazole 30 mg daily for two weeks. On the 14th night mean nocturnal (2100-0700) intragastric acidity was significantly decreased by 75% (p less than 0.001). At 0700, 22 hours after the last dose of omeprazole, there were significant increases in the bacterial count and the nitrite and N-nitrosamine concentrations in the gastric juice (p less than 0.001). Three days later these changes had resolved. Short term treatment of healthy volunteers with omeprazole is associated with a short lived increase in the gastric bacterial flora, with endogenous production of N-nitroso compounds.